E-governance through social media: an analysis on the use of Facebook and Twitter by Indian Government - Saroj A.; Pal S. (My University, 2025)
The study explores the adoption of social media (SM) by 46 ministries of the Government of India. This trend is new in India but steadily increasing. We analyse how government ministries use SM, particularly Twitter and Facebook, to disseminate information, engage with stakeholders and take feedback on government initiatives. The study, based on three years of SM data analysis, captures activities, discussion topics, inter-connectedness, public engagement, and popularity of GoI ministries. Among eight different SM channels that GoI ministries use, Twitter and Facebook are the most common and popular ones. Primary topics of discussion are meetings and projects like Prime Minister's (PM) projects, railways projects, GST, and different development schemes. The Ministry of Railways and the Ministry of Agriculture post maximum in SM, but the PM's account is followed by the most. The Ministry of Information and Broadcasting serves as a coordinator with a good hub, authority, and PageRank score. © 2023 Inderscience Enterprises Ltd.